Geospatial Analysis and Modelling of Urban Structure and Dynamics - Jiang, Bin.; Yao, Xiaobai; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The increasingly urbanized world has created various problems of environment, climate, consumption of resources, and public health, which are closely linked to the side-effects of urbanization such as sprawl, congestion, housing affordability and loss of open space. Fundamental to the urban problems are two separate yet related issues: urban structure and urban dynamics. The chapters collected in this book present an excellent profile of the current state of geospatial analysis and modelling, and demonstrate how these approaches can contribute to the study of various urban issues. The book addresses key themes including new ways of capturing data digitally at the individual level, the development of systems based around networks, the notion of linking hierarchy to networks to morphology as in complexity theory, and the development of new ways of integrating diverse urban processes through simulation paying careful attention to the basic econometric and statistical principles of spatial analysis. With a foreword by Michael Batty and an epilog by Michael F. Goodchild
Geospatial Analysis and Modeling of Urban Structure and Dynamics: An Overview -- Individual-Based Data Capture for Modeling Urban Structure and Dynamics -- High-Resolution Geographic Data and Urban Modeling: The Case of Residential Segregation -- Space Syntax and Pervasive Systems -- Decentralized Spatial Computing in Urban Environments -- Modeling Urban Complexity and Hierarchy -- Network Cities: A Complexity-Network Approach to Urban Dynamics and Development -- Scaling Analysis of the Cascade Structure of the Hierarchy of Cities -- Simulating and Modeling Urban Transportation Systems -- The Dilemma of On-Street Parking Policy: Exploring Cruising for Parking Using an Agent-Based Model -- Multiscale Modeling of Virtual Urban Environments and Associated Populations -- Imageability and Topological Eccentricity of Urban Streets -- A Spatial Analysis of Transportation Convenience in Beijing: Users$1 (BPerception Versus Objective Measurements -- Object-Oriented Data Modeling of an Indoor/Outdoor Urban Transportation Network and Route Planning Analysis -- Analyzing and Modeling Urban Grown, Urban Changes and Impacts -- Integration of Remote Sensing with GIS for Urban Growth Characterization -- Evaluating the Ecological and Environmental Impact of Urbanization in the Greater Toronto Area through Multi-Temporal Remotely Sensed Data and Landscape Ecological Measures -- Modeling Urban Effects on the Precipitation Component of the Water Cycle -- Interpolating a Consumption Variable for Scaling and Generalizing Potential Population Pressure on Urbanizing Natural Areas -- Modeling Cities as Spatio-Temporal Places -- Studying Other Urban Problems Using Geospatial Analysis and Modeling -- Geospatial Analysis and Living Urban Geometry -- Analyzing Spatial Patterns of Late-Stage Breast Cancer in Chicago Region: A Modified Scale-Space Clustering Approach -- Influence of Job Accessibility on Housing Market Processes: Study of Spatial Stationarity in the Buffalo and Seattle Metropolitan Areas -- How do Socioeconomic Characteristics Interact with Equity and Efficiency Considerations? An Analysis of Hurricane Disaster Relief Goods Provision -- Visualizing and Diagnosing Coefficients from Geographically Weighted Regression Models.s
Keywords: Geography; Geographical information systems; Regional planning; Architecture; Human Geography; Geography; Geographical Information Systems/Cartography.; Cities, Countries, Regions; Human Geography; Urbanism; Landscape/Regional and Urban Planning